FERROELECTRIC THIN FILMS FOR NEUROMORPHIC COMPUTING: SYNTHESIS, CHARACTERIZATION, AND DEVICE INTEGRATION - Nurul Huda; Amin Zaki; Nong Chai; Siti Shofiah (Yayasan Adra Karima Hubbi, 2025)
The limitations of conventional von Neumann computing architectures in handling complex, data-intensive tasks have spurred significant interest in brain-inspired neuromorphic computing. A critical challenge in this field is the development of hardware that can efficiently emulate the synaptic plasticity of biological neurons. This study focuses on the synthesis, characterization, and integration of ferroelectric thin films, specifically hafnium zirconium oxide (HZO), as a promising material platform for creating artificial synaptic devices. The primary objective was to fabricate high-quality HZO thin films and demonstrate their capacity to mimic key synaptic functions. HZO films were synthesized using pulsed laser deposition, followed by comprehensive characterization of their structural, ferroelectric, and electrical properties using XRD, PFM, and I-V measurements. The optimized films were then integrated into two-terminal memristive device structures. The resulting devices successfully exhibited essential synaptic behaviors, including potentiation, depression, and spike-timing-dependent plasticity (STDP), with low energy consumption per synaptic event. The gradual and controllable modulation of ferroelectric domain switching was identified as the core mechanism enabling this analog-like resistance modulation.